On the (mis-) alignment of consumer and social welfare in markets with network effects - Irina Suleymanova; Christian Wey (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze duopoly Bertrand competition under network effects. We consider both incompatible and compatible products. Our main result is that network effects create a fundamental conflict between the maximization of social welfare and consumer surplus whenever products are incompatible. While consumer surplus is highest in the symmetric equilibrium, social welfare is highest in the asymmetric equilibrium. We also show that both consumer surplus and social welfare are higher in any equilibrium under compatibility when compared with incompatible products. However, .firms never have strict incentives to achieve compatibility. Finally, we show the robustness of our results when products are horizontally differentiated.
Keywords: D43; L13; 330; Bertrand duopoly; network effects; (In-) compatibility; welfare; Duopol; Produktdifferenzierung; Network Externalities; Normung; Wettbewerb; Konsumentenrente; Soziale Wohlfahrtsfunktion; Wohlfahrtseffekt; Theorie